The prophets of Israel - Kratz, Reinhard Gregor, 1957-; Hagedorn, Anselm C.; MacDonald, Nathan, 1975- (Winona Lake, Indiana : Eisenbrauns, 2015)
"The book offers an up-to-date and readable introduction to the manifold literary and historical problems of biblical prophecy. Reinhard Gregor Kratz provides the reader with a clear analysis of the development of the institution of prophecy in ancient Israel and Second Temple Judaism. Through a close reading of the prophetic corpus he demonstrates that in biblical tradition we have to distinguish between the historical and the literary prophet"--
Includes bibliographical references and indexes.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Bible. -- Criticism, interpretation, etc; Bible; RELIGION / Biblical Studies / Prophets; Criticism, interpretation, etc; Electronic books